AKSARA BALI DALAM UPACARA DWIJATI DI GRIYA AGUNG BANGKASA, DESA BONGKASA KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Yadnya Manuaba, I Gede Sugata (PANGKAJA: JURNAL AGAMA HINDU, 2019)
The Balinese letters in the ritual of dwijàti (coronation) of a Balinese Priest, it’s really very complex and many used. The letters of Bali in the ritual of dvijàti is used called the letter of modre and wijàksara. Both the meaning is magic syllables. Both of letters mostly paint (rajah) in the plain white cloth as shroud or winding sheet, and at the body of the candidate, and many tools of this ritual also. In this research toned at the Balinese letters above. The formulation of problems in this research comprises of the forms, function and the meanings of Balinese letters at the cloths of sedaraga (ritual of dead body) at Griya Agung Bangkasa, the Bongkasa village, district of Abiansemal, Badung regency, Bali province. The theory used in this research comprises the theory of symbols, the functional structural theory and semiotic theory. The results of this research include the forms of many letter of Balinese written in the cloth shroud or winding sheet, at the body of the candidates and many tools of this rituals. The functions include religious function, magic, expressive, inspiration and aestetics-decoration. The meaning of the Balinese letters of the ritual of dvijati include the theologically meaning, education, socio-religious, socio-cultural and solidarity.